Pembiasaan Personal Hygiene untuk Penerapan Pola Hidup Sehat dan Bersih Bagi Siswa Sekolah Dasar - Arnelia Dwi Yasa; Denna Delawanti (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
Schools must prepare the infrastructure needed to implement the New Normal during the Covid-19 pandemic. For example, providing hand washing facilities in each room, hand sanitizer, masks, thermometers, disinfectants, and disinfectant sprayers. All of these infrastructure facilities must be owned by schools for the implementation of the New Normal. SDN Purwodadi 01 is an elementary school located in Malang City. The number of facilities or places for washing hands at the school is limited. The habit of frequently washing hands or using hand sanitizers for students at SDN Purwodadi 01 is still not done periodically, especially by grade 4 students. Therefore, it is necessary to provide personal hygiene in maintaining cleanliness. The purpose of this service activity is the habit of personal hygiene for the application of a clean and healthy lifestyle for elementary school students. Service activities are carried out using the lecture method, question and answer and assignments. The lecture method was used to explain and provide an understanding of how to wash hands properly, the importance of using masks at school, and the habit of using hand sanitizers when carrying out activities at school. Students are also facilitated to ask the service team. In the assignment method, students are given pre-test and post-test questions to determine the level of student understanding regarding personal hygiene. The results of the evaluation showed that students' knowledge related to personal hygiene was categorized as moderate.